2000
DOI: 10.7164/antibiotics.53.50
|View full text |Cite
|
Sign up to set email alerts
|

Arisugacins C and D, Novel Acetylcholinesterase Inhibitors and Their Related Novel Metabolites Produced by Penicillium sp. FO-4259-11.

Abstract: The mutant of Penicillium sp. FO-4259, an arisugacins A and B producing strain, was found to produce a series of metabolites, designated arisugacins C, D, E, F, G and H, which were structurally related to arisugacins A and B. These compoundswere isolated from the culture broth and the physico-chemical and biological properties were examined. The IC50

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
53
0
8

Year Published

2000
2000
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 7 publications
8
53
0
8
Order By: Relevance
“…On the other hand, characteristic signals of aromatic hydrogens and methyl angular groups can be observed in some spectra and may indicate the presence of well known Penicillium anticholinesterasic metabolites such as quinolactacins or arisugacins (e.g. Kuno et al 1996;Otoguro et al 2000;Kim et al 2001;Santos & Rodrigues-Filho 2002).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…On the other hand, characteristic signals of aromatic hydrogens and methyl angular groups can be observed in some spectra and may indicate the presence of well known Penicillium anticholinesterasic metabolites such as quinolactacins or arisugacins (e.g. Kuno et al 1996;Otoguro et al 2000;Kim et al 2001;Santos & Rodrigues-Filho 2002).…”
Section: Resultsmentioning
confidence: 97%
“…Similarly, some researchers have previously reported high selective AChE inhibitory activity by different compounds such as quinolactacins A1 and A2 produced by Penicillium citrinum (Kim et al 2001), arisugacins A, B, C and D with the structurally related compounds territrems B and C produced by Penicillium sp. (Kuno et al 1996;Otoguro et al 2000), and terreulactones A, B, C, and D produced by Aspergillus terreus (Kim et al 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Subsequently, we studied the introduction of a hydroxy group at the 12a position via epoxidation. Epoxidation of 9 to yield 19 with m-CPBA or DMDO was inefficient, and oxidation with t-BuOOH in the presence of Mo(CO) 6 34 gave the best results, although this was only a 29% yield. For the following epoxide opening reaction to obtain 20, we examined various conditions, including LiAlH 4 , Super-H w , and Birch reduction, but none of them was successful (Scheme 5).…”
Section: Construction Of the Arisugacin Skeletonmentioning
confidence: 91%
“…Therefore, the absolute configurations at C-3, C-4a, C-6a, C-12a, and C-12b of 1f were assigned as S,R,R,R, and S, respectively, based on the previously elucidated relative stereochemistry. 6 To determine the absolute configuration of territrem B (2), we prepared its MTPA esters by subjecting 2 to enone hydrogenation followed by reduction with NaBH 4 to give 6. NOE correlations from H-12a-OH to H-1-OH and from H-1 to H-12 in 6 indicated that the 1-hydroxy group was oriented toward the a-side (Scheme 2).…”
Section: Determination Of the Absolute Stereochemistries Of Arisugacinsmentioning
confidence: 99%
See 1 more Smart Citation